Challenging cases in rheumatic disease pregnancy: management perspectives from reproductive rheumatologists - Mani, Iswariya; Bermas, Bonnie; Edens, Cuoghi; Sammaritano, Lisa; Zell, JoAnn; Birru Talabi, Mehret (Frontiers in Lupus, 2024)
Pregnant females with rheumatic and musculoskeletal diseases (RMD) have a higher risk of adverse pregnancy and perinatal outcomes than individuals without RMDs. Evidence-based guidelines have been developed for the reproductive health care and management of these individuals, yet multiple areas of uncertainty exist around diagnosis and treatment of the pregnant patient with confirmed or suspected RMD. We present a series of several outpatient cases that address areas of uncertainty in the field of reproductive rheumatology. Expert opinions were elicited from rheumatologists who have expertise in reproductive health in the RMDs to build new understanding around diagnosis or treatment approaches. Cases focused on the interpretation of antiphospholipid antibodies in various clinical scenarios, diagnosis and management of nephrotic-range proteinuria during pregnancy, and the use of tumor-necrosis factor inhibitors during pregnancy. Our objective was not to replace available guidelines and classification criteria, but rather to provide a range of expert opinions that a rheumatologist might consider when tailoring treatment and care for patients in their own practices and when faced with challenging situations in which limited data exist.